Trusmi's Written Batik Manufacturer Industry and Its Impact on Trusmi's Trusmi's Batik Written Creator in the Village Trusmi Kulon Cirebon - Ai Nety Sumidartini (Majalah Ilmiah Bijak, 2021)
Batik industry is now growing. Likewise with batik Trusmi that development is now growing rapidly. Revenue is a consequence or impact of the development of batik industry. Revenue Trusmi batik artisans, can be used for the basic needs of both basic needs and the needs of batik artisans in the business of making batik and batik artisans revenue also used for industrial development or business Trusmi batik. The problems discussed in this esearch on the impact of batik artisans Trusmi revenue as a result of the development of batik industry Trusmi. With the goal, which is to determine the revenue impact of batik artisans Trusmi batik industry development.The method used in this research is using descriptive qualitative method with the approach used approach SWOT analysis (Strength, Weakness, Opportunity, Threath). Data collected by using observation and in-depth interviews with batik artisans Trusmi and also the village, as well as gathering documentation in the form of images and small notes.Results of research conducted by the researchers, it is known that income Trusmi batik artisans used for a variety of needs, not only for the basic needs of batik artisans but is also used to develop the Business of making batik. By using SWOT analysis of the impact of this revenue is not only powerful, but also has the disadvantage of not yet arranged neatly on the financial statements batik business, and there were also threats, in the form of batik competition from other regions. While the strength of itself is able to carry on business batik and opportunities that can develop the business of making or write Trusmi batik industry. With the aim to maximize profits and the opportunities and minimize weaknesses and threats to the batik artisans need to develop the business by using a strategy of differentiation.Â